Dr Frank C. Baxter, titan of US educational television. (June 2014) - Smith, Jacob
Abstract : Dr Frank C. Baxter, an English Professor at the University of Southern California, emerged as a prominent figure in the movement for US educational television in the early 1950s. As the instructor of one of the first televised university courses, Shakespeare on TV, Baxter garnered national press coverage and managed a remarkable crossover to mainstream television stardom. Baxter's success relied in large part on his dynamic performances, which worked to resolve some of the contradictions inherent in the 'television professor' at this time. Baxter 1 s career supplements existing historical work on early television stardom and performance, since it prompts us to recognize the university lecture as a cultural tradition that fed into early television performance. The educators, reformers, and philanthropists who comprised the movement for educational television (ETV) struggled to find camera-friendly performers who could strike the perfect balance between pedagogy and diversion. Baxter's television appearances were held up as a paradigm for how teaching and media entertainment could coexist, and his career has new relevance as university instructors struggle with online teaching initiatives like massive open online courses (MOOCs) and iTunes U.